Dakwah Moderasi dan Kebangsaan: Strategi Al-Jam'iyatul Washliyah dalam Menguatkan Wawasan Kebangsaan di Era Disrupsi - Kurniawan, Rhohis; Suparto, Suparto (Ad-DA'WAH, 2025)
This study examines Al-Jam'iyatul Washliyah's moderate da'wah strategy in strengthening national insight in the digital disruption era. Al-Washliyah, established in 1930, has historically served as a mediator between traditional and modern Islamic thought. In the digital disruption era, challenges to religious moderation have become increasingly complex with online radicalization, religious hoaxes, and social polarization. This research employs a descriptive qualitative method with library research approach. The findings reveal that Al-Washliyah implements moderate da'wah strategies through four main pillars: education based on religious moderation, rahmatan lil alamin da'wah, inclusive social charity, and economic empowerment. In the digital era, Al-Washliyah transforms its strategy through social media platform optimization, religious digital literacy development, cross-organizational collaboration, and strengthening moderate cadre networks. These strategies have proven effective in maintaining interfaith harmony and strengthening Pancasila national insight. Keywords: Al-Jam'iyatul Washliyah, religious moderation, national insight, digital da'wah, disruption era